On the derivations of Leibniz algebras of low dimension - Kurdachenko, L.A.; Semko, M.M.; Yashchuk, V.S. (Доповіді НАН України, 2023)
Let L be an algebra over a field F. Then L is called a left Leibniz algebra if its multiplication operations [⋅, ⋅] additionally satisfy the so-called left Leibniz identity: [[a,b],c] = [a,[b,c]] – [b,[a,c]] for all elements a, b, c ∈ L. In this paper, we begin the description of the algebra of derivations of Leibniz algebras having dimension 3. It is clear that the description of the algebra of derivations of all Leibniz algebras, having dimension 3, is quite large. Therefore, in this article, we will focus on the description of the nilpotent Leibniz algebra, whose nilpotency class is 3, and the nilpotent Leibniz algebra, whose center has dimension 2. Нехай L — це алгебра над полем F. Тоді L називається лівою алгеброю Лейбніца, якщо її операції множення [⋅, ⋅] задовольняють так звану ліву тотожність Лейбніца: [[a, b], c] = [a, [b, c]] – [b, [a, c]] для всіх елементів a, b, c ∈ L. У статті започатковано опис алгебри похідних алгебр Лейбніца, що мають вимірність 3. Зрозуміло, що опис алгебри похідних всіх алгебр Лейбніца вимірності 3 є досить великим. Тому тут наведено опис нільпотентних алгебр Лейбніца, клас нільпотентності яких дорівнює 3, та нільпотентних алгебр Лейбніца, центр яких має розмірність 2.